Should COVID-19 vaccines be mandated in schools? - an international caregiver perspective. Issue 36 (26th August 2022) - Baumer-Mouradian, Shannon H.; Hart, Rebecca J.; Bone, Jeffrey N.; Seiler, Michelle; Olson, Prasra; Keitel, Kristina; Manzano, Sergio; Gualco, Gianluca; Krupik, Danna; Schroter, Stephanie; Weigert, Rachel M.; Chung, SunHee; et al.
Highlights: 37% of caregivers opposed vaccine mandates at all school levels. Only 20% of caregivers agreed with immediate vaccine mandates. Vaccine safety was the most important concern regarding vaccine mandates. 26% of caregivers would remove their child from school if vaccines became mandated. Abstract: Objectives: Caregiver attitudes toward mandating COVID-19 vaccines for their children are poorly understood. We aimed to determine caregiver acceptability of COVID-19 vaccine mandates for schools/daycares and assess if opposition to mandates would result in removal of children from the educational system. Study Design: Perform a cross-sectional, anonymous survey of adult caregivers with children ≤ 18 years presenting to 21 pediatric emergency departments in the United States, Canada, Israel, and Switzerland, November 1st through December 31st, 2021. The primary outcome was caregiver acceptance rates for school vaccine mandates, and the secondary outcomes included factors associated with mandate acceptance and caregiver intention to remove the child from school. Results: Of 4, 393 completed surveys, 37% of caregivers were opposed to any school vaccine mandate. Caregiver acceptance was lowest for daycare settings (33%) and increased as the child's level of education increased, college (55%). 26% of caregivers report a high likelihood (score of 8–10 on 0–10 scale) to remove their child from school if the vaccine became mandatory. Child safety was caregivers' greatest concern over vaccine mandates. A multivariable model demonstrated intent to vaccinate their child for COVID-19 (OR = 8.9, 95% CI 7.3 to 10.8; P < 0.001) and prior COVID-19 vaccination for the caregiver (OR = 3.8, 95% CI 3.0 to 4.9; P < 0.001) had the greatest odds of increasing mandate acceptance for any school level. Conclusions: Many caregivers are resistant to COVID-19 vaccine mandates for schools, and acceptance varies with school level. One-fourth of caregivers plan to remove their child from the educational system if vaccines become mandated.